Androgen Receptor-Target Genes in African American Prostate Cancer Disparities. (10th January 2013) - Wang, Bi-Dar; Yang, Qi; Ceniccola, Kristin; Bianco, Fernando; Andrawis, Ramez; Jarrett, Thomas; Frazier, Harold; Patierno, Steven R.; Lee, Norman H.
Abstract : The incidence and mortality rates of prostate cancer (PCa) are higher in African American (AA) compared to Caucasian American (CA) men. To elucidate the molecular mechanisms underlying PCa disparities, we employed an integrative approach combining gene expression profiling and pathway and promoter analyses to investigate differential transcriptomes and deregulated signaling pathways in AA versus CA cancers. A comparison of AA and CA PCa specimens identified 1, 188 differentially expressed genes. Interestingly, these transcriptional differences were overrepresented in signaling pathways that converged on the androgen receptor (AR), suggesting that the AR may be a unifying oncogenic theme in AA PCa. Gene promoter analysis revealed that 382 out of 1, 188 genes contained cis -acting AR-binding sequences. Chromatin immunoprecipitation confirmed STAT1, RHOA, ITGB5, MAPKAPK2, CSNK2A, 1 and PIK3CB genes as novel AR targets in PCa disparities. Moreover, functional screens revealed that androgen-stimulated AR binding and upregulation of RHOA, ITGB5, and PIK3CB genes were associated with increased invasive activity of AA PCa cells, as siRNA-mediated knockdown of each gene caused a loss of androgen-stimulated invasion. In summation, our findings demonstrate that transcriptional changes have preferentially occurred in multiple signaling pathways converging ("transcriptional convergence") on AR signaling, thereby contributing to AR-target gene activation and PCa aggressiveness in AAs.